Intervención educativa en el manejo adecuado de pacientes con traumatismo craneoencefálico producidos por accidentes de tránsito dirigido a profesionales de atención prehospitalario del Cantón Riobamba. - Paredes Padilla, Cecilia Pilar (2025)
The aim of the current research is to design an educational intervention guide to improve the management of traumatic brain injury(TBI) by prehospital care professionals. A quantitative, cross-sectional, and exploratory methodology was used. Data were collected using a validated instrument administered by prehospital care providers in Riobamba, with prior approval from the Bioethics Committee at the National University of Chimborazo. The results identified significant knowledge gaps,particulary in cerebral metabolism (50%), intracranial (33,3%),cerebral perfusion (33,3%),mean arterial (20%),and assessment of consciousness levels (13.33%).These findings highlight the urgent need to strengthen clinical competencies in TBI management supporting the development of a targeted educational guide as a strategy for professional development.